Incidence and management of metabolic acidosis with sodium bicarbonate in the ICU: An international observational study - Fujii, T; Udy, AA; Nichol, A; Bellomo, R; Deane, AM; El-Khawas, K; Thummaporn, N; Serpa Neto, A; Bergin, H; Short-Burchell, R; Chen, C-M; Cheng, K-H; et al. (BioMed Central, 2021)
Background Metabolic acidosis is a major complication of critical illness. However, its current epidemiology and its treatment with sodium bicarbonate given to correct metabolic acidosis in the ICU are poorly understood. Method This was an international retrospective observational study in 18 ICUs in Australia, Japan, and Taiwan. Adult patients were consecutively screened, and those with early metabolic acidosis (pH < 7.3 and a Base Excess < –4 mEq/L, within 24-h of ICU admission) were included. Screening continued until 10 patients who received and 10 patients who did not receive sodium bicarbonate in the first 24 h (early bicarbonate therapy) were included at each site. The primary outcome was ICU mortality, and the association between sodium bicarbonate and the clinical outcomes were assessed using regression analysis with generalized linear mixed model. Results We screened 9437 patients. Of these, 1292 had early metabolic acidosis (14.0%). Early sodium bicarbonate was given to 18.0% (233/1292) of these patients. Dosing, physiological, and clinical outcome data were assessed in 360 patients. The median dose of sodium bicarbonate in the first 24 h was 110 mmol, which was not correlated with bodyweight or the severity of metabolic acidosis. Patients who received early sodium bicarbonate had higher APACHE III scores, lower pH, lower base excess, lower PaCO2, and a higher lactate and received higher doses of vasopressors. After adjusting for confounders, the early administration of sodium bicarbonate was associated with an adjusted odds ratio (aOR) of 0.85 (95% CI, 0.44 to 1.62) for ICU mortality. In patients with vasopressor dependency, early sodium bicarbonate was associated with higher mean arterial pressure at 6 h and an aOR of 0.52 (95% CI, 0.22 to 1.19) for ICU mortality. Conclusions Early metabolic acidosis is common in critically ill patients. Early sodium bicarbonate is administered by clinicians to more severely ill patients but without correction for weight or acidosis severity. Bicarbonate therapy in acidotic vasopressor-dependent patients may be beneficial and warrants further investigation.